1986
DOI: 10.3346/jkms.1986.1.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Immunological abnormalities in patient with IgA nephropathy

Abstract: T cell immunity and phagocytic activity were studied in the blood of patients with IgA nephropathy in order to clarify their roles in the pathogenesis of IgA nephropathy. The percentages of total T lymphocytes, helper T cell and suppressor T cells were significantly reduced in patients. A significantly elevated helper T cell/suppressor T cell ratio in patients showed a predominant reduction in suppressor T cells. There was a significant relationship between histologic findings and helper T cell/suppressor T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the pathogenesis of IgA nephropathy is not well defined, it is suggested that immunoregulatory dysfunciton plays a major role 1 5 ) . In IgA nephropathy, many evidences of immunological involvements such as the elevated level of serum IgA 30 ) and the circulating IgA immune complexes 31 34 ) , the deposition of IgA in dermal capillaries, liver, lung, and gut 35 , 52 ) , and the recurrence of original disease in renal allograft 36 ) were demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenesis of IgA nephropathy is not well defined, it is suggested that immunoregulatory dysfunciton plays a major role 1 5 ) . In IgA nephropathy, many evidences of immunological involvements such as the elevated level of serum IgA 30 ) and the circulating IgA immune complexes 31 34 ) , the deposition of IgA in dermal capillaries, liver, lung, and gut 35 , 52 ) , and the recurrence of original disease in renal allograft 36 ) were demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immunopathogenesis of IgA nephropathy is not completely defined, it is suggested that immunoregulatory dysfunction plays an important role in the pathogenesis of IgA nephropathy 1 5 ) . Recent studies also suggest the association between the disordered immunoregulation of T cell and the disease activity of IgA nephropathy 6 – 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…S5B). Previous two studies have suggested that the decrease in number and function of NK cells were associated with the disease progression of IgAN [ 31 , 32 ]. Altered monocyte gene expression patterns and numbers were found to be pathogenic factors in IgAN [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yano N [ 53 ] reported that HLA-DR-positive NK cells were significantly increased in IgA nephropathy patients, and HLA-DR-positive NK cells had greater ability to produce IFN-γ than HLA-DR-negative NK cells, thus exacerbating kidney injury [ 54 ]. Previous studies have shown that the decline in the number and function of NK cells was closely related to the disease progression of IgA nephropathy [ 55 , 56 ]. Recently Zeng H [ 13 ] further confirmed through single-cell RNA-sequencing that total NK (CD56 + CD3 ±) and NK-1 and NK-2 (CD56 + CD3-) cell numbers were significantly reduced in IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%